Joan Roís de Corella i els límits de la literatura - Cingolani, Stefano M. (Caplletra. Revista Internacional de Filologia, 1998)
In a text that anticipates and sums up part of the thesis defended in Joan Roís de Corella: La importància de dir-se honest [the importance of being honest], the author shows the poet as creator of an autonomous literary fiction basedon the mimesis of Aristotle' s Poètics, which distances the reader from the text and at the same time generates cathartis,piety and moral reflection.